An evaluation of environmental impact assessment procedure in the Lesotho Highlands Water Project : Phase 1 - Nkopane, Setenane (Department of Environmental and Geographical Science, 2016)
Environmental Impact Assessment is a procedure that ensures that the environmental consequences of development proposals are understood and adequately considered in the planning process. This important project planning requirement is often inadequately addressed in many developing countries - especially with regard to dam projects. Lesotho is a small developing country in Southern Africa which is currently engaged in a multi-phased dam project - the Lesotho Highlands Water Project (LHWP) - in order to utilize its most abundant natural resource - water. Planning for the LHWP incurred some irregularities, particularly with regard to environmental implications. The purpose of this study is to evaluate the environmental impact assessment procedures of the LHWP, Phase lA. This includes review of the environmental studies that were carried out and the findings of these studies; assessment of the familiarity of the Lesotho Highlands Development Authority (LHDA) staff with EIA procedures; and examination of the extent to which the communities in the project area were consulted regarding this project. The study is based on two surveys: firstly, within the Environment Division of the Lesotho Highlands Development Authority to assess the familiarity of staff members with proper EIA procedures. In this survey 28 self-administered questionnaires were issued, and 23 were collected. Secondly, structured interviews and unstructured group discussions were carried out in 14 villages to examine the extent to which the communities affected by the LHWP had been involved in the environmental impact assessments of Phase lA; and whether the impacts they experienced and the subsequent. Mitigation efforts had been considered comprehensively by the project proponents. Eighty interviews were conducted in six of the 14 villages selected in the study, in the remaining villages data was collected through group discussions. The groups consisted of 10 - 12 members (usually prominent persons) from the community. The study revealed that EIA for Phase 1 A of the LHWP was not carried out according to recognized standards. Environmental studies that were undertaken were done too late in the EIA process, and did riot facilitate the project planning. The study also found that the majority of LHDA staff members are not familiar with the details of the EIA process, and did not participate in Phase lA project planning. The communities affected by the LHWP were not given the opportunity to raise their concerns about the project. This is manifested by the magnitude and type of impacts which they have incurred because of the LHWP. Members of these communities therefore regard their livelihoods as being worse than before the project. It is thus recommended that LHDA should revise and significantly improve its project planning approaches - especially for the subsequent phases of the project. It is imperative· to incorporate public participation in the EIAs of these phases. Formulation of guideline sand legislation - in Lesotho as a whole - will ensure enforcement and compliance with sound environmental assessment procedures, and improve on LHDA's manpower capabilities with regard to EIA and environmental management. This in turn will enhance an environmentally sustainable development.